False alarmism: technological disruption and the U.S. labor market, 1850–2015 - Atkinson, Robert D.; Wu, John (Information Technology & Innovation Foundation, 2017)
"Contrary to popular perceptions, the labor market is not experiencing unprecedented technological disruption. In fact, occupational churn in the United States is at a historic low. It is time stop worrying and start accelerating productivity with more technological innovation."